2012
DOI: 10.1177/1753944712461164
|View full text |Cite
|
Sign up to set email alerts
|

Altered regional blood flow distribution in Mas-deficient mice

Abstract: These results suggest that the Ang-(1-7)/Mas axis plays an important role in regional and systemic hemodynamic adjustments in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
2
26
1
Order By: Relevance
“…Accordingly, cardiomyocytes from Mas-KO mice presented a smaller peak Ca 2+ transient and slower Ca 2+ uptakes due to a decreased expression of SERCA2 (Gomes et al, 2012). These changes were turned into a decreased heart function in Mas-KO mice (Santos et al, 2006;Botelho-Santos et al, 2012;Gava et al, 2012). The changes in the calcium handling proteins were paralleled by changes in the NO production machinery (Dias-Peixoto et al, 2008).…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 67%
See 1 more Smart Citation
“…Accordingly, cardiomyocytes from Mas-KO mice presented a smaller peak Ca 2+ transient and slower Ca 2+ uptakes due to a decreased expression of SERCA2 (Gomes et al, 2012). These changes were turned into a decreased heart function in Mas-KO mice (Santos et al, 2006;Botelho-Santos et al, 2012;Gava et al, 2012). The changes in the calcium handling proteins were paralleled by changes in the NO production machinery (Dias-Peixoto et al, 2008).…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 67%
“…It has been reported that Mas-deficient mice present an important increase in the vascular resistance in many territories, such as kidney, lung, adrenal gland, mesentery, spleen, and brown fat tissue (Botelho-Santos et al, 2012). A parallel increase in total peripheral resistance and a decreased cardiac index was also observed.…”
Section: Mas-related G Protein-coupled Receptors and Mas In Cardiomentioning
confidence: 71%
“…In humans and other species, the endothelial layer of blood vessels produce Ang(1-7) (Santos and Baracho, 1992) and the presence of MAS in endothelial cells and VSMC is conserved, suggesting localized functional interaction da Costa Goncalves et al, 2007;Sampaio et al, 2007b;Xu et al, 2008). Mas knockout increases the vascular resistance in mice in various organs (Botelho-Santos et al, 2012). In the transgenic rats, with increased circulating Ang (1)(2)(3)(4)(5)(6)(7), an Ang(1-7)-dependent vasodilatory tone in blood vessels is suggested.…”
Section: G Pathophysiological Evidence Of Mas Receptor Interaction Wmentioning
confidence: 99%
“…In addition the Mas knockout, mice are also reported to have changes in hemostasis (Fraga-Silva et al, 2008) and penile fibrosis (da Costa Goncalves et al, 2007). A common mechanism behind the Mas knockout mice, exhibiting altered heart rate and blood pressure, increased vascular resistance, and decrease blood flow, is thought to be endothelial dysfunction due to imbalances in nitric oxide (NO) and reactive oxygen species (Castro et al, 2005;da Costa Goncalves et al, 2007;Peiro et al, 2007;Rabelo et al, 2008;Xu et al, 2008;Raku san et al, 2010;Botelho-Santos et al, 2012).…”
Section: F Mas Gene-knockout In Micementioning
confidence: 99%
See 1 more Smart Citation